GAYA BAHASA PERBANDINGAN DAN PERTENTANGAN DALAM NOVEL BUMI DAN LUKANYA KARYA REVIANA APRILLIANDINI DAN RELEVANSINYA TERHADAP PEMBELAJARAN BAHASA INDONESIA - Risma; Daeng, Kembong; Nurhusna (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe: (1) the form and meaning of comparative and contrasting language styles contained in the novel Bumi dan Lukanya by Reviana Aprilliandini, (2) the relevance of comparative and contrasting language styles in the novel Bumi dan Lukanya by Reviana Aprilliandini to Indonesian language learning. This type of research is qualitative descriptive research with a library study method. The data in this study are in the form of narrative excerpts, dialogues, and descriptions containing comparative and contrasting language styles in the novel Bumi dan Lukanya by Reviana Aprilliandini. The data source for this study is the novel Bumi dan Lukanya by Reviana Aprilliandini. The data collection technique is carried out through careful reading techniques, taking notes, and classifying data based on the type and meaning of comparative and contrasting language styles according to the focus of the research. The research instrument is the researcher herself who is assisted by a data corpus sheet and a comparative and contrasting language style indicator sheet. Data analysis uses the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study show that: (1) The forms of language style in the novel Bumi dan Lukanya contain various forms of comparative language style, such as simile, metaphor, personification, allegory, and antithesis, as well as opposing language style, such as hyperbole, litotes, irony, oxymoron, satire, paradox, cynicism and sarcasm, while the meaning of the comparative and contradictory language style functions to strengthen the image of the characters, inner self, and story so that the message conveyed becomes more vivid and profound (2) The comparative and contrasting style of language in the novel Bumi dan Lukanya has relevance to Indonesian language learning, especially in the material on linguistic element analysis, and can be used as a learning resource to improve students' critical thinking skills and short story writing skills.